A cross-sectional study to assess the epidemiologic profile and complications among chickenpox patients in an infectious disease hospital in a Metropolitan city - G., Prahatheeswaran; Sai M. B., Abhinand; Sable, Pavan Laxman (International Journal Of Community Medicine And Public Health, 2023)
Background: Chickenpox is a highly contagious and acute disease caused by the varicella-zoster virus. According to a WHO position paper, varicella has a global disease burden of 140 million infections, 42 million severe sequelae, and 4200 fatalities every year. Chickenpox affects 16 persons per 1,000 people annually in wealthy countries. With a case fatality rate of 3 per 1,000 instances annually, 3% of these cases have problems, and 5% require hospitalization. This cross-sectional study assesses the epidemiological determinants & complications among the patients admitted to infectious disease hospitals. Methods: It was a descriptive, cross sectional and hospital based study. Total duration of study was 18 months (Jan 2020 -August 2021), conducted in infectious hospital of a metropolitan city. A total of 453 patients with confirmed diagnosis of chickenpox and getting admitted in the infectious disease hospital .were selected as study subjects and interviewed by a validated questionnaire. Results: A total of 453 chickenpox patients were included in the study and because of covid pandemic situation only 118 samples are interviewed of which 91 (77.1%) were males, remaining 27 (22.9%) were females and all 118 (100%) patients presented with rash which is the diagnostic feature of chickenpox, out of that 106 had fever, 84 had cough, 74 had malaise and 32, 17 patients had shivering and backache respectively. Conclusions: It was found that about one-quarter of cases recorded were in the age group of 19–40 years. This group most probably comprised those who missed the vaccination when they were children. Health education among the general population is suggested to reduce the secondary cases by early diagnosis and vaccination and isolation to reduce the burden of diseases.